2017
DOI: 10.1080/13636820.2017.1410724
|View full text |Cite
|
Sign up to set email alerts
|

Preventive behaviour at work of vocational students

Abstract: Background. Statistics suggest young workers are a group at high risk of sustaining injury. Vocational students are frequently included in the 'young workers' group, with all other different types of workers aged 24 or less. However, the literature exposes vocational students as having specific descriptive characteristics, suggesting that this subgroup might differ from other 'young workers'. The literature offers little description of this population toward prevention at work. The aim of the study was to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Therefore, FA training prepares students to respond to crises and offers timely and effective care for many occurrences. 25 Concerning the knowledge mean score about basic first aid concepts, the present study findings showed that there was a statistically significant (p≤0.01) improvement in the mean scores of the post-test and follow-up test. These findings are consistent with Balai &Tripathi.…”
Section: Discussionsupporting
confidence: 44%
“…Therefore, FA training prepares students to respond to crises and offers timely and effective care for many occurrences. 25 Concerning the knowledge mean score about basic first aid concepts, the present study findings showed that there was a statistically significant (p≤0.01) improvement in the mean scores of the post-test and follow-up test. These findings are consistent with Balai &Tripathi.…”
Section: Discussionsupporting
confidence: 44%
“…As a result, other routes emerged to meet the needs of skilled workers in the construction sector, which was far from the standard. In addition, other factors such as job descriptions and the work environment also have a role in developing workers' competencies [20].…”
Section: Discussionmentioning
confidence: 99%
“…Students' unsafe behavior causes most accidents at educational institutions. Young workers are at a greater risk of occupational injuries and accidents [5]. According to Guerin et al [6], an estimated 3.2 million non-fatal injuries occurred among young workers (aged 15-24 years) during 2012-2018.…”
Section: Introductionmentioning
confidence: 99%